Isothermal kinetic study of nitric oxide adsorption and decomposition on Pd(111) surfaces: molecular beam experiments - Thirunavukkarasu, K; Thirumoorthy, K; Libuda, X; Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2005)
The kinetics of NO adsorption and dissociation on Pd(111) surfaces and the NO sticking coefficient (S-NO) were probed by isothermal kinetic measurements between 300 and 525 K using a molecular beam instrument. NO dissociation and N-2 productions were observed in the transient state from 425 K and above on Pd(l 11) surfaces with selective nitrogen production. Maximum nitrogen production was observed between 475 and 500 K. It was found that, at low temperatures, between 300 and 350 K, molecular adsorption occurs with a constant initial SNO of 0.5 until the Pd(I 11) surface is covered to about 70-80% by NO. Then SNO rapidly decreases with further increasing NO coverage, indicating typical precursor kinetics. The dynamic adsorption-desorption equilibrium on Pd(I 11) was probed in modulated beam experiments below 500 K. CO titration experiments after NO dosing indicate the diffusion of oxygen into the subsurface regions and beginning surface oxidation at >= 475 K. Finally, we discuss the results with respect to the rate-limiting character of the different elementary steps of the reaction system.

Molecular beam study of the NO plus CO reaction on Pd(111) surfaces - Thirunavukkarasu, K; Thirumoorthy, K; Libuda, J; Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2005)
Nitric oxide (NO) reduction with carbon monoxide (CO) on the Pd(111) surface was studied under isothermal conditions by molecular beam techniques as a function of temperature, NO:CO beam composition, and beam flux. Systematic experiments were performed under transient and steady state conditions. Displacement of adsorbed CO by NO in the transient state of the reaction was observed at temperatures between 375 and 475 K for all the NO: CO compositions studied. NO accumulation occurs on Pd(l 11) surface under steady state conditions, below 475 K, due to stronger chemisorption of NO. The steady state reaction rates attain a maximum at about 475 K, nearly independent of beam composition. N-2 was found to be the major product of the reduction, along with a minor production of N2O. The production of N2 and N2O indicates molecular and dissociative adsorption of NO on Pd(l 11) at temperatures up to 525 K. Postreaction TPD measurements were performed in order to determine the nitrogen coverage under steady-state conditions. Finally, the results are discussed with respect to the rate-controlling character of the different elementary steps of the reaction system.